Qualitative Observational Research in the Intensive Care Setting: A Personal Reflection on Navigating Ethical and Methodological Issues - Fredrika Sundberg CCRN, PhD; Sue Kirk; Berit Lindahl CCRN, PhD (SAGE Publishing, 2021)
The aim of this theoretical paper is to critically reflect on the ethical and methodological issues that arose during a study that observed nurses' care-giving in an intensive care unit setting. The authors critically discuss the methodological and ethical issues as well as the practical realities that were encountered when evaluating a complex intervention using unstructured qualitative observations. We describe the process with negotiating access and entering into the clinical field. Moreover, we reflect on experiences related to methodological issues such as the observer role, how to construct field notes, and how to encounter ethical dilemmas and other problems when being an observer in a closed and protected setting like an intensive care unit. We argue that qualitative observations give an insider perspective when studying the conditions for health and well-being. Our experiences can be transferred to other contexts and guide researchers interested in doing qualitative observational studies.